2006
DOI: 10.1007/s11104-006-9082-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil water, nutrient availability and sapling survival under organic and polyethylene mulch in a seasonally dry tropical forest

Abstract: We examine the effect of mulches on the soil volumetric water content (SVWC), pH, carbon (C), total and mineral (NH 4 and NO 3 ) nitrogen (N), total and bicarbonate phosphorus (P), and on the survival and relative growth rate of three species, Ipomea wolcottiana Rose, Lonchocarpus eriocarinalis Micheli and Caesalpinia eriostachys Benth, in a degraded seasonally dry tropical forest (SDTF) area. Our study year was unusually dry, with only half of the mean annual rainfall. Sixteen plots (5 · 6 m) for each of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Moreover, maintenance of a high soil fertility is important to obtain a consistently high yield of sweet sorghum. Soil fertility can be effectively improved by the application of organic matter such as crop residue, legumes, and animal manure compost, because these materials offer beneficial effects for soil physiochemical and biological properties, thereby increasing plant growth and yields (Othieno, 1973;Anderegg and Naylor, 1988;Barajas-Guzmán et al, 2006;Fang et al, 2007). After squeezing sugar juice out of a sweet sorghum stem, a large amount of residue (bagasse), a type of organic matter, is generated.…”
Section: N N Uptake N Loss Sweet Sorghum Bagassementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, maintenance of a high soil fertility is important to obtain a consistently high yield of sweet sorghum. Soil fertility can be effectively improved by the application of organic matter such as crop residue, legumes, and animal manure compost, because these materials offer beneficial effects for soil physiochemical and biological properties, thereby increasing plant growth and yields (Othieno, 1973;Anderegg and Naylor, 1988;Barajas-Guzmán et al, 2006;Fang et al, 2007). After squeezing sugar juice out of a sweet sorghum stem, a large amount of residue (bagasse), a type of organic matter, is generated.…”
Section: N N Uptake N Loss Sweet Sorghum Bagassementioning
confidence: 99%
“…The reason for this higher efficiency when using both IF and SSB surface application is not clear; however, it might result from differences in the balance between N assimilation and C consumption in komatsuna (Osone and Tateno, 2003). Moreover, SSB surface application might affect soil physiochemical and biological attributes in the plant-soil system, such as soil water content, microorganisms, and phosphorus uptake in komatsuna, which consequently have positive effects on komatsuna yield (Othieno, 1973;Barajas-Guzmán et al, 2006). In contrast, the combination of IF and SSB incorporation led to a lower yield than that obtained in the treatment with IF alone.…”
Section: Effects Of Ssb On Komatsuna Growth Yield and N Uptakementioning
confidence: 99%
“…Many studies confirm that mulches can protect the soil against erosion (Bautista et al 1996), release nutrients to the soil via decomposition (Fang et al 2007), moderate soil moisture loss and temperature fluctuations (O'Connell et al 2004) and decrease weed growth (Kathiresan 2007). Other studies, however, have found that mulching may have no effect or even a negative effect on seedling growth or weed suppression (Bulmer 2000;Heiskanen and Rikala 2006;Cole 2007), and it has been suggested that the effects of mulching vary greatly according to the site, plant species and mulch types (Barajas-Guzmán et al 2006;Huang et al 2008). Nevertheless, the impact of mulching on the regeneration of native species in forest ecosystems has been the subject of little attention, and the results of some studies are contradictory (cf.…”
Section: Introductionmentioning
confidence: 99%
“…www.elsevier.com/locate/foreco Available online at www.sciencedirect.com Forest Ecology and Management 255 (2008) [1802][1803][1804][1805][1806][1807][1808][1809] Use of mulch in perturbed areas protects the soil and reduces water and nutrient losses (Shock et al, 1997;Paris et al, 1998;Barajas-Guzmán et al, 2006). The potential of mulch to improve soil structure, increase organic matter, and establish patterns of nutrient cycling has also been recognized (Yohannes, 1999;Tiquia et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the utility of mulching has been assessed both in the establishment of broadleaf and conifer plantations (Davies, 1988a,b;Walker and McLaughlin, 1989;Gupta, 1991;Truax and Gagnon, 1993;Haywood, 1999;Green et al, 2003) and in reforestation efforts following intensive logging in western and northern North American forests (Flint and Childs, 1987;Houle and Babeux, 1994). Mulching is highly beneficial in dry tropical areas and especially on steep land with high rainfall intensity; however, mulch materials vary with respect to improving soil physical characteristics and fertility (Khan et al, 1988;Roe et al, 1993;Pinamonti, 1998;Haywood, 1999;Acosta-Martínez et al, 1999;Tiquia et al, 2002;Erhart and Hartl, 2003;Barajas-Guzmán et al, 2006;Cook et al, 2006). Green et al (2003) indicated that results from mulching studies in forestry applications have been mixed, with beneficial effects in some cases and not in others.…”
Section: Introductionmentioning
confidence: 99%